Controversies regarding and perspectives on clinical utility of biomarkers in hepatocellular carcinoma - Song, Pei-Pei (World J Gastroenterol, 2016)
The prevalence of hepatocellular carcinoma (HCC) worldwide parallels that of persistent infection with the hepatitis B virus (HBV) and/or hepatitis C virus (HCV). According to recommendations by the World Health Organization guidelines for HBV/HCV, alpha-fetoprotein (AFP) testing and abdominal ultrasound should be performed in routine surveillance of HCC every 6 mo for high-risk patients. These examinations have also been recommended worldwide by many other HCC guidelines over the past few decades. In recent years, however, the role of AFP in HCC surveillance and diagnosis has diminished due to advances in imaging modalities. AFP was excluded from the surveillance and/or diagnostic criteria in the HCC guidelines published by the American Association for the Study of Liver Diseases in 2010, the European Association for the Study of the Liver in 2012, and the National Comprehensive Cancer Network in 2014. Other biomarkers, including the Lens culinaris agglutinin-reactive fraction of AFP (AFP-L3), des-γ-carboxyprothrombin, Dickkopf-1, midkine, and microRNA, are being studied in this regard. Furthermore, increasing attention has focused on the clinical utility of biomarkers as pre-treatment predictors for tumor recurrence and as post-treatment monitors. Serum and tissue-based biomarkers and genomics may aid in the diagnosis of HCC, determination of patient prognosis, and selection of appropriate treatment. However, further studies are needed to better characterize the accuracy and potential role of these approaches in clinical practice.